Rumination and Sleep Quality Among Older Adults: Examining the Role of Social Support. (30th December 2020) - Marini, Christina M; Wilson, Stephanie J; Nah, Suyoung; Martire, Lynn M; Sliwinski, Martin J
Abstract: Objectives: Although the adverse link between rumination and sleep quality is well established, much of the literature neglects the role of social factors. This study examined the role of older adults' perceived social support from spouses and from family/friends in modifying the association between trait rumination and sleep quality. Existing hypotheses suggest that social support may play 3 unique roles, each tested within the current study: (H1) support may act as a protective factor that buffers negative effects of rumination on sleep quality, (H2) support may curtail rumination and, in turn, promote sleep quality, and (H3) rumination may erode support and, in turn, undermine sleep quality. Method: Data came from 86 partnered older adults in independent-living or retirement communities ( M age = 75.70 years). We utilized 3 waves of interview data collected annually between 2017 and 2019. The first hypothesis was tested using moderation in multilevel models; the second 2 hypotheses were evaluated with prospective associations using multilevel mediation. Results: Negative effects of high-trait rumination on time-varying sleep quality were attenuated among those who reported high, stable levels of support from their spouses. Perceived family/friend support did not yield the same protective effect. There was no evidence that support preempted, or was eroded by, rumination. Discussion: Perceived spousal support may act as a psychosocial resource that mitigates negative effects of trait rumination on older adults' sleep quality. Interventions aimed at mitigating maladaptive outcomes of rumination on sleep quality for older adults should consider spousal support as a key target.